Kebijakan penghematan anggaran dan dampaknya terhadap kesejahteraan publik: Tinjauan Siyasah Maliyah terhadap Inpres No. 1 tahun 2025 - Habibulloh, Luqman Hakim (Maliki Interdisciplinary Journal, 2025)
Presidential Instruction (Inpres) No. 1 of 2025 establishes a substantial budget austerity policy, targeting a reduction in government spending of up to IDR 306 trillion. This measure is taken in response to the global economic slowdown, primarily to maintain national fiscal stability. This study analyzes the policy from the perspective of siyasah maliyah, an Islamic discipline concerning public financial governance. The main focus of siyasah maliyah lies in upholding the principles of justice, public welfare (maslahah), and equitable wealth distribution. To achieve its objectives, the study adopts a descriptive qualitative approach based on library research, using secondary data including official government documents, relevant literature on Islamic public finance, and reports from national media. The findings of this study indicate that although the austerity policy aims to ensure fiscal sustainability, the reduction in budget allocations for vital public sectors such as education and health poses significant risks. The potential decline in public access to essential basic services raises concerns of contradiction with the principles of maqashid shariah, the higher objectives of Islamic law that emphasize the protection of public interest. From the perspective of siyasah maliyah, budget policy formulation should consistently prioritize the safeguarding of the fundamental rights of society. To overcome financial constraints, the study proposes the optimization of Islamic financial instruments such as zakat, waqf, and the management of baitul mal as potential alternative sources of funding. Based on this analysis, it is recommended that the government reconsider the austerity policy, taking into account the Islamic principle of distributive justice as a core foundation for policy-making.